Effects of Heat-Moisture Treatment on the Digestibility and Physicochemical Properties of Waxy and Normal Potato Starches - Guihong Fang; Ke Liu; Qunyu Gao (Foods, 2022)
Heat-moisture treatment (HMT) is a safe, environmentally friendly starch modification method that reduces the digestibility of starch and changes its physicochemical properties while maintaining its granular state. Normal potato starch (NPS) and waxy potato starch (WPS) were subjected to HMT at different temperatures. Due to erosion by high-temperature water vapor, both starches developed indentations and cracks after HMT. Changes were not evident in the amylose content since the interaction between the starch molecules affected the complexation of amylose and iodine. HMT increased pasting temperature of NPS from 64.37 °C to 91.25 °C and WPS from 68.06 °C to 74.44 °C. The peak viscosity of NPS decreased from 504 BU to 105 BU and WPS decreased from 384 BU to 334 BU. The crystallinity of NPS decreased from 33.0% to 24.6% and WPS decreased from 35.4% to 29.5%. While the enthalpy values of the NPS declined from 15.74 (J/g) to 6.75 (J/g) and WPS declined from 14.68 (J/g) to 8.31 (J/g) at 120 °C. The solubility and swelling power of NPS decreased while that of WPS increased at 95 °C. Due to the lack of amylose in WPS, at the same HMT processing temperature, the reduction in peak viscosity of treated WPS compared to that of native starch was smaller than that of NPS. The resistant starch (RS) content of NPS after HMT at 120 °C was 73.0%. The slowly digestible starch (SDS) content of WPS after HMT at 110 °C was 37.6%.